Chitosan Nanoparticles as Bioactive Vehicles for Textile Dyeing: A Proof of Concept - Costa, Eduardo M.; Silva, Sara; Machado, Manuela; Sousa, Sérgio C.; Tavaria, Freni K.; Pintado, Manuela (Polymers, 2022)
In recent years bioactive textiles have risen to the forefront of consumers perception due to their potential protection against virus, fungi and bacteria. However, traditional textile staining is an eco-damaging process that and current methods of textile functionalization are expensive, complicated and with great environmental impact. With that in mind, this work sought to show a possible solution for this problematic through the usage of a novel one step textile dyeing and functionalization method based upon nanoencapsulated textile dyes (NTDs). To do so navy blue everzol NTDs were produced with chitosan, cotton dyed, characterized through FTIR and SEM and biological potential evaluated through biocompatibility screening and antimicrobial activity against skin pathogens. The data obtained showed that NTDs effectively dyed the target textile through a coating of the cotton fibre and that NTDs formed hydrogen bonds with the cellulose fibre via electrostatic interactions of the chitosan amino groups with cotton sulphate groups. From a biocompatibility perspective NTDs dyed cotton had no deleterious effects upon a skin cell line, as it promoted cellular metabolism of HaCat cells, while traditionally died cotton reduced it by 10%. Last but not least, NTDs dyed cotton showed significant antimicrobial activity as it reduced viable counts of MRSA, MSSA and A. baumannii between 1 and 2 log of CFU while traditional dyed cotton had no antimicrobial activity. Considering these results the novel method proposed shows is a viable and ecological alternative for the development of antimicrobial textiles with potential biomedical applications.